2007
DOI: 10.1002/humu.20371
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor mutations are the principal cause of renal type 1 pseudohypoaldosteronism

Abstract: Aldosterone plays a key role in electrolyte balance and blood pressure regulation. Type 1 pseudohypoaldosteronism (PHA1) is a primary form of mineralocorticoid resistance characterized in the newborn by salt wasting, hyperkalemia, and failure to thrive. Inactivating mutations of the mineralocorticoid receptor (MR; NR3C2) are responsible for autosomal dominant and some sporadic cases of PHA1. The question as to whether other genes may be involved in the disease is of major importance because of the potential li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…6 These patients can improve with age, and some adult patients are usually asymptomatic and have fewer abnormal biochemical findings (e.g., only lifelong increases in aldosterone or hyperkalemia). 9,10 To date, approximately 50 distinct mutations in the human MR gene and approximately 20 mutations in ENaC genes responsible for PHA1 have been described. 11,12 However, some patients, especially those with sporadic PHA1, do not have genetic abnormalities in MR or ENaC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 These patients can improve with age, and some adult patients are usually asymptomatic and have fewer abnormal biochemical findings (e.g., only lifelong increases in aldosterone or hyperkalemia). 9,10 To date, approximately 50 distinct mutations in the human MR gene and approximately 20 mutations in ENaC genes responsible for PHA1 have been described. 11,12 However, some patients, especially those with sporadic PHA1, do not have genetic abnormalities in MR or ENaC.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, some patients, especially those with sporadic PHA1, do not have genetic abnormalities in MR or ENaC. 6,10,[13][14][15] Because PHA1 is life-threatening and many probands may be missed as a result of early death, additional genetic mechanisms might participate in its pathogenesis. According to recent studies, aldosterone resistance may also be associated with a reduction in MR expression, probably mediated by transcriptional mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…omim.org/) and Orphanet (http://www.orpha.net/) under numbers MIM#177735 and ORPHA#71871) is a mild form of primary mineralocorticoid resistance and represents the most frequent form of the disease. It is due to loss-offunction mutations in the NR3C2 gene (Geller et al 1998, Sartorato et al 2003, Pujo et al 2007). The prevalence, as estimated from recruitment through a national reference center for rare diseases (MC.…”
Section: Pseudohypoaldosteronism Typementioning
confidence: 99%
“…Most cases of autosomal dominant PHAI link to mutations in the mineralocorticoid receptor (MR). 3 In general, patients with autosomal recessive PHAI, as opposed to patients with autosomal dominant PHAI, have a more severe clinical phenotype and do not spontaneously improve during early childhood. Furthermore, given the generalized expression of ENaC in epithelial tissues, autosomal recessive PHAI associates with systemic manifestations, most notably, recurrent pulmonary infections.…”
Section: Phai and Phaiimentioning
confidence: 99%
“…Detailed studies of different MR mutations show that mutations can affect the N-terminal region, ligand-binding domain, or DNA-binding domain. 3 Although functional studies using various MR reporter assays showed that causative mutations associate with less MR activation in response to aldosterone, Geller et al 4 studied MR mutations in six families with autosomal dominant PHAI and reported novel insights regarding some mutations. In one kindred, there was a C1984T mutation that converted G590 into a stop codon.…”
Section: Phai and Phaiimentioning
confidence: 99%